Cohomological correlations for sets of singular points of the actions of $Z/4$ group by $(S^n)^k$ - Plakhta , L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We investigate $Z/2$-graded cohomology modules with coefficients in the field $F_2$ of sets of singular points of the complex actions of the group $Z/4$ on spaces $X$ whose cohomology rings are isomorphic to $H* ((S^n)^k, F_2)$.